Silicification patterns in wheat leaves related to ontogeny and soil silicon availability under field conditions - Schaller, Jörg; Puppe, Daniel; Busse, Jaqueline; Paasch, Silvia; Katz, Ofir; Brunner, Eike; Kaczoreck, Danuta; Sommer, Michael (Plant and Soil, 2022)
Purpose: Silicon (Si) accumulation is an important strategy for plant defense against biotic and abiotic stress. Solid amorphous silica (ASi) deposits have been found to protect plants against different stressors (e.g., drought stress, ultraviolet radiation, herbivory, and pests). Most research on ASi deposits and their subsequent function is conducted under lab conditions. However, it is still unclear at which stage in ontogeny ASi deposits are developed to fulfill their function in plant protection under field conditions. Methods: We combined SEM–EDX, NMR spectroscopy, and Si extractions to analyze silicification patterns in wheat leaves (blades and sheaths) in relation to ontogeny and soil Si availability. Results: Silicification patterns in wheat leaves varied strongly in intensity between four different growth stages (tillering, stem extension, heading, and grain filling) and ASi deposition did not just continuously increase over the growing season. Newly formed leaf tissues showed relatively low Si concentrations, which increased over time. A high condensation state of the silica bodies and trichomes was found at all growth stages, referring to a high rigidity of the silica bodies. Conclusions: Our results indicate that development of ASi deposits in wheat leaves depends on growth stage and Si availability. Detailed knowledge on solid ASi deposition in wheat during ontogeny and its consequences for stress mitigation is crucial for farmers worldwide.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Crops; Plant growth stage; Plant protection; Silica; Silica bodies; Silicon availability; Triticum aestivum